Effect of polarization on the microstructure and piezoelectric properties of PZT-Cement composites - A. Chaipanich (2018)
Lead zirconate titanate (PZT)-Portland cement (PC) composites were produced and successfully poled at different poling field and time. The effect of polarization on the microstructure and piezoelectric properties were then investigated. It was found that, at a fixed poling field up to 2 kV/mm, the piezoelectric coefficient (d33) was found to increase with poling time. The optimum poling time was found at 45 minutes where d33 value is 42 pC/N. The optimum and most practical poling field found for the composite was at 2 kV/mm. Lower poling field would give the composite lower piezoelectricity and poling field that is too high would result to breakdown of samples. Therefore, from these results, a poling field of 2 kV/mm at 45 minutes would be the ideal polarization condition used in poling PZT-PC composites. © 2008 Trans Tech Publications, Switzerland.